Managing diversity : expert solutions to everyday challenges. (Pocket mentor series., 2009)
This title teaches managers how to recruit a diverse team; foster an inclusive environment by replacing common misperceptions with facts; handle diversity-related conflict; and how to tap the business value generated by the team's diversity.